ANALISA YURIDIS PERTANGGUNG JAWABAN DIREKSI PADA PENGADAAN BARANG/JASA DI PT. BANK SUMUT (STUDI : PUTUSAN TIPIKOR PENGADILAN NEGERI MEDAN NO. 93/PID.SUS-TPK/2016/PN.MDN. JO. PUTUSAN PENGADILAN TINGGI MEDAN NO. 06/PID.SUS-TPK/2017/PN.MDN.) - Muhammad Iqbal; Sunarmi Sunarmi; Budiman Ginting; Faisal Akbar (Universitas Sumatera Utara, 2018)
ABSTRACT The Board of Directors shall be the management of the company representing the company, both inside and outside the court. The legal norms implied in the provision that all corporate liabilities, both represent and management of the company, are on the shoulders of directors. In accordance with Article 97 paragraph (2) of Law no. 40 of 2007 regarding Limited Liability Company, states that: